A self-sustaining high-strength wastewater treatment system using solar-bio-hybrid power generation - Bustamante Román, Mauricio (2017)
This study focuses on system analysis of a self-sustaining high-strength wastewater treatment concept combining solar technologies, anaerobic digestion, and aerobic treatment to reclaim water. A solar bio-hybrid power generation unit was adopted to power the wastewater treatment. Concentrated solar power (CSP) and photovoltaics (PV) were combined with biogas energy from anaerobic digestion. Biogas is also used to store the extra energy generated by the hybrid power unit and ensure stable and continuous wastewater treatment. It was determined from the energy balance analysis that the PV-bio hybrid power unit is the preferred energy unit to realize the self-sustaining high-strength wastewater treatment. With short-term solar energy storage, the PV-bio-hybrid power unit in Phoenix, AZ requires solar collection area (4032 m2) and biogas storage (35 m3), while the same unit in Lansing, MI needs bigger solar collection area and biogas storage (5821 m2 and 105 m3, respectively) due to the cold climate.